Fact or Fiction, It Is Time for a Verdict on Vasculogenic Mimicry? - Valdivia, Andrés; Mingo, Gabriel; Aldana, Varina; Pinto, Mauricio P.; Ramirez, Marco; Retamal, Claudio; Gonzalez, Alfonso; Nualart, Francisco; Corvalan, Alejandro H.; Owen, Gareth I. (Frontiers in Oncology, 2019)
The term vasculogenic mimicry (VM) refers to the capacity of certain cancer cells to form fluid-conducting structures within a tumor in an endothelial cell (EC)-free manner. Ever since its first report by Maniotis in 1999, the existence of VM has been an extremely contentious issue. The overwhelming consensus of the literature suggests that VM is frequently observed in highly aggressive tumors and correlates to lower patient survival. While the presence of VM in vivo in animal and patient tumors are claimed upon the strong positive staining for glycoproteins (Periodic Acid Schiff, PAS), it is by no means universally accepted. More controversial still is the existence of an in vitro model of VM that principally divides the scientific community. Original reports demonstrated that channels or tubes occur in cancer cell monolayers in vitro when cultured in matrigel and that these structures may support fluid movement. However, several years later several papers emerged stating that connections formed between cancer cells grown on matrigel represented VM. We speculate that this became accepted by the cancer research community and now the vast majority of the scientific literature reports both presence and mechanisms of VM based on intercellular connections, not the presence of fluid conducting tubes. In this opinion paper, we call upon evidence from an exhaustive review of the literature and original data to argue that the majority of in vitro studies presented as VM do not correspond to this phenomenon. Furthermore, we raise doubts on the validity of concluding the presence of VM in patient samples and animal models based solely on the presence of PAS+ staining. We outline the requirement for new biomarkers of VM and present criteria by which VM should be defined in vitro and in vivo.